Shielding the oil reserves: the scutellum as a source of chemical defenses. Issue 4 (9th February 2022) - Murphy, Katherine M; Poretsky, Elly; Liu, Huijun; Micic, Nikola; Nyhuis, Annika; Bohlmann, Joerg; Schmelz, Eric A; Zerbe, Philipp; Huffaker, Alisa; Bjarnholt, Nanna
Abstract : The cereal scutellum is a hub for diverse specialized defense metabolism and pathway discovery.